2019
DOI: 10.3390/molecules24122253
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effect of Dietary Taurine Supplementation on Grouper (Epinephelus coioides): A 1H-NMR-Based Metabolomics Study

Abstract: Taurine is an indispensable amino acid for many fish species and taurine supplementation is needed when plant-based diets are used as the primary protein source for these species. However, there is limited information available to understand the physiological or metabolic effects of taurine on fish. In this study, 1H nuclear magnetic resonance (NMR)-based metabolomic analysis was conducted to identify the metabolic profile change in the fish intestine with the aim to assess the effect of dietary taurine supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
2
18
0
2
Order By: Relevance
“…Besides, TUR makes the feed highly palatable because of its animal origin, whereas most formulas used in fish meals are of plant origin, which makes them less palatable for fish, thereby decreasing food consumption [ 34 ]. Similar growth-enhancing effects of TUR-supplemented diet were reported for white shrimp, Litopenaeus vannamei [ 52 ]; O. niloticus [ 38 ]; orange-spotted grouper, Epinephelus coioides [ 53 ]; and African catfish, Clarias gariepinus [ 54 , 55 ]. Moreover, a TUR-supplemented diet could improve the growth of common carp exposed to salinity stress (10 ppt range) for eight weeks [ 54 ].…”
Section: Discussionsupporting
confidence: 57%
“…Besides, TUR makes the feed highly palatable because of its animal origin, whereas most formulas used in fish meals are of plant origin, which makes them less palatable for fish, thereby decreasing food consumption [ 34 ]. Similar growth-enhancing effects of TUR-supplemented diet were reported for white shrimp, Litopenaeus vannamei [ 52 ]; O. niloticus [ 38 ]; orange-spotted grouper, Epinephelus coioides [ 53 ]; and African catfish, Clarias gariepinus [ 54 , 55 ]. Moreover, a TUR-supplemented diet could improve the growth of common carp exposed to salinity stress (10 ppt range) for eight weeks [ 54 ].…”
Section: Discussionsupporting
confidence: 57%
“…However, the whole-body protein content in cobia (Rachycentron canadum) was increased with dietary taurine content (Watson et al 2013). Also, grouper (Epinephelus coioides) fed dietary taurine improved amino acid uptake and protein synthesis by the actions of metabolic regulation in the protein synthesis pathway (Shen et al 2019). So, taurine has improved the protein metabolism in fish by optimizing the mitochondrial protein synthesis and TOR gene expression.…”
Section: Protein Metabolismmentioning
confidence: 99%
“…In addition, lipase activity in the intestine of juvenile black carp (M. piceus) and turbot (Scophthalmus maximus) was significantly increased with taurine supplementation in low fish meal diet (Zhang et al 2018(Zhang et al , 2019. Meanwhile, dietary taurine increased the lipid metabolism of grouper (Epinephelus coioides) by optimizing the lipid digestion and metabolic regulation (Shen et al 2019). Thus, taurine has important roles in lipid metabolism in fish, including bile acid synthesis, lipid emulsification, lipid digestion and absorption, and body lipid deposition.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…In aquaculture, dietary taurine improves growth, regulates immunity, and enhances the antioxidant capacity in crab (Eriocheir sinensis) [41]. Taurine supplementation affects the metabolome, improves energy utilization and amino acid uptake, promotes protein, lipid, and purine synthesis, and accelerates growth in grouper (Epinephelus coioides) [42]. However, Kortner et al indicated that dietary supplementation with 0.4% taurine in salmon does not relieve gut enteritis, which is the first pathogenic stage of vibriosis with enteritis [43].…”
Section: Discussionmentioning
confidence: 99%